Eksistensi Perbudakan di Era Modern: Memahami Human Trafficking dan Ajaran Moral Al-Qur’an - Iqrimatunnaya, Iqrimatunnaya (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
Humanism as a theory of personality formation, places humans as the most perfect creatures created by God with noble potential to establish harmonious social relationships. However, human rights violations, such as human trafficking, remain a major challenge in Indonesia. So, the author tries to conduct a direct dialectic with the Qur'an to get an interpretation of the verses of slavery in the context of human trafficking and formulate steps to prevent it in Indonesia. This research uses a qualitative method with the analytical knife of Hans Georg-Gadamer's fusion of horizon theory. The results showed that QS. Yusuf: 19-20, QS. an-Nur: 33, and QS. ash-Shura: 42 after being analyzed using Gadamer's hermeneutics shows that slavery and human trafficking have occurred since ancient times. However, in today's horizon, Islam not only emphasizes the liberation of slaves, but also prohibits human exploitation in all its forms. Therefore, the solutions offered include moral education, economic empowerment, law enforcement, and rehabilitation for victims as concrete steps in combating human trafficking.